2020
DOI: 10.3390/cryst10010022
|View full text |Cite
|
Sign up to set email alerts
|

Pb(Er1/2Nb1/2)O3–Pb(Zn1/3Nb2/3)O3–PbTiO3 Single Crystals with High Curie Temperature

Abstract: In this work, 0.15Pb(Er1/2Nb1/2)O3–0.63Pb(Zn1/3Nb2/3)O3–0.22PbTiO3 (15PEN–63PZN–22PT) single crystals with a pure perovskite structure are obtained through the flux method. The phase structure, dielectric, ferroelectric properties and upconversion photoluminescence of the crystals are studied. The ternary crystals along the [110] orientation have a high Curie temperature (Tc = 250 °C) and large coercive field (Ec = 11.0597 kV/cm) which are higher than those of crystals reported previously. Furthermore, the PEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Under a 980 nm laser excitation, the modified crystals produce up-conversion with three colors [blue (480 nm), strong near-infrared (804 nm), and weak red (652 nm)]. Chen et al (2020b) and Chen et al (2020c) reported the coercive field E c of Eu doped PZN-9PT crystal significantly increased to 11.0597 kV/cm, and it is triple higher than that of pure PZN-9PT crystal. Besides, under the excitation of 464 nm, four broadband peaks appear at around 593 nm, 613 nm, 657 nm, and 716 nm, respectively.…”
Section: Rare-earth Doped Lead-based Single Crystalsmentioning
confidence: 99%
“…Under a 980 nm laser excitation, the modified crystals produce up-conversion with three colors [blue (480 nm), strong near-infrared (804 nm), and weak red (652 nm)]. Chen et al (2020b) and Chen et al (2020c) reported the coercive field E c of Eu doped PZN-9PT crystal significantly increased to 11.0597 kV/cm, and it is triple higher than that of pure PZN-9PT crystal. Besides, under the excitation of 464 nm, four broadband peaks appear at around 593 nm, 613 nm, 657 nm, and 716 nm, respectively.…”
Section: Rare-earth Doped Lead-based Single Crystalsmentioning
confidence: 99%